The Impact of the Value of Religiosity on Buying Decision Making on the Overseas Bugis Community in Jambi - Kurniati Karim; Ahmad Hosen (Publisher Cv. Inara, 2020)
The Bugis tribe is one of the tribes in South Sulawesi Province, in addition to the Makassar and Toraja tribes, who uphold their religion and become the basis for their behavior. This is in accordance with the Bugis philosophy of